Effect of Electrode Gap and Electric Field Strength in Corona Wind Drying on Drying Kinetics, Color Changes and Shrinkage of Ripe Mango - Choosri, Withu; Choosri, Touchpong (Journal of Food Technology, Siam University, 2022)
This research was to study the effect of the electrode gap and electric field strength in corona wind drying on drying kinetics, color changes and shrinkage by using the static temperature and velocity at 50 oC and 1.0 m/s. The generation of corona wind was determined from the interval gap between electrodes 3, 4 and 5 cm. and the electric field strength at 0 (non-electric), 4 and 8 kV/cm., respectively. The results showed that the decrease of the electrode gap and increase of the electric potential difference resulted in an increase of the effective diffusivity coefficient (Deff), while the total color differences (∆E*) and the product shrinkage decreased. In addition, the optimum conditions for corona drying were the electrode gap at 3 cm. and the electric potential difference at 8 kV/cm. These optimum conditions led to decrease of the drying time and caused the color and shrinkage quality of drying product was better than that from hot air drying.